Indefeasible Family Rights: A Comparative View on the Restrictions of Testamentary Freedom. Issue 2 (May 2018) - Roggendorf, Hannah
Abstract : Testamentary freedom and family protection in succession law are often described as contradictory principles. Nonetheless, in most European legal systems both principles coexist. This article focuses on three conceptions of this coexistence: legal rights in Scotland, compulsory portion in Germany and family provision in England. All three systems must accommodate changing values of family life in modern society. Most recently, the timeliness of traditional solutions has been a controversial topic of the debate leading to the Succession (Scotland) Act 2016, and it continues to be an issue of debate, because regarding legal rights no final solution has been found. A comparative analysis can demonstrate the interconnectedness between social values and legal concepts, and it can further identify potential for legal innovation. Family rights, especially in Germany, have been contextualised with a historic notion of family property. In the present law of all three countries the contextual emphasis shifts towards familial solidarity and a moral duty to provide for family members. On a concrete level, there is a discernible connection between matrimonial property relationships and spousal rights to the estate in Germany and England, which in Scotland is no longer present. Further, the English system can also accommodate cohabitants as potential claimants. Scots law has at least in the case of intestacy incorporated a similar provision, while German law thus far does not provide any legal concept for cohabitation.